2013
DOI: 10.3856/vol41-issue1-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface patterns of Sotalia guianensis (Cetacea: Delphinidae) in the presence of boats in Port of Malhado, Ilheus, Bahia, Brazil

Abstract: ABSTRACT.Interactions with boats can cause several behavioural changes in cetaceans. The purpose of this research is to analyse if Guiana dolphins, Sotalia guianensis, change their surfacing patterns in the presence of different boat categories, and their contact distances to boats at Port of Malhado, Ilhéus, Bahia, Brazil. Data were collected from a fixed point from September 2008 to August 2009 and totalled 362.6 h of sampling effort and 213.22 h of effective effort. The number of dolphin breathing events wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Fewer surfacing events were performed by the dolphins in the presence of any boat type. Increased dive time during motorboat encounters was evidenced for this same population in the Port of Malhado, Ilhéus (Santos et al, 2013) and for different cetacean species: Chinese white dolphins (Ng & Leung, 2003), Irrawaddy dolphins (Orcaella brevirostris, Kreb & Rahadi, 2004), and bottlenose dolphins (Arcangeli & Crosti, 2009). These animals react to boat proximity with escape strategies, rising fewer times to the surface to reduce their exposure (Frid & Dill, 2002;, and moving away from the source of disturbance (Lusseau, 2003).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Fewer surfacing events were performed by the dolphins in the presence of any boat type. Increased dive time during motorboat encounters was evidenced for this same population in the Port of Malhado, Ilhéus (Santos et al, 2013) and for different cetacean species: Chinese white dolphins (Ng & Leung, 2003), Irrawaddy dolphins (Orcaella brevirostris, Kreb & Rahadi, 2004), and bottlenose dolphins (Arcangeli & Crosti, 2009). These animals react to boat proximity with escape strategies, rising fewer times to the surface to reduce their exposure (Frid & Dill, 2002;, and moving away from the source of disturbance (Lusseau, 2003).…”
Section: Discussionmentioning
confidence: 71%
“…An encounter occurred when a boat was at a distance of fewer than 100 m from the closest dolphin. The 100 m distance of encounter definition was based on Valle & Melo (2006) and Santos et al (2013) studies on S. guianensis. Encounter distance was estimated visually since the duration of surfacing events of Guiana dolphins are too short for telemeter use.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these coastal habitats have been occupied and significantly altered by human settlements and infrastructure (Meirelles, 2020;Schiavetti et al, 2020). Various human threats have been reported for the species, such as incidental capture in fishing gear (Monteiro-Neto et al, 2000;Meirelles et al, 2002;Crespo et al, 2010;Meirelles et al, 2010;Bertozzi, Silva & Flach, 2020), chemical pollution (Santos-Neto et al, 2014;Alonso et al, 2015;Dorneles et al, 2016;Lailson-Brito et al, 2020), noise pollution (Bittencourt et al, 2017;Pais et al, 2018;Rossi-Santos, Monteiro-Filho & Azevedo, 2020), unregulated dolphin-watching activities (Santos-Junior et al, 2006;Valle & Melo, 2006;Filla & Monteiro-Filho, 2009), boat traffic (Santos, Schiavetti & Alvarez, 2013;Schiavetti et al, 2020), and harbour operations, such as dredging (Meirelles, 2013). Infectious diseases such as morbillivirus (Groch et al, 2018;Flach et al, 2019), herpesvirus (Sacristán et al, 2018), brucellosis (Sánchez-Sarmiento et al, 2019), and toxoplasmosis (Silva et al, 2019) have been reported for Guiana dolphins and are of great concern, as outbreaks can cause mass die-offs (Carvalho et al, 2020).…”
Section: Introductionmentioning
confidence: 99%